167 A case of rapidly progressive meningoencephalitis caused by amoebae in the UK. Issue 6 (27th May 2022) - Surendranathan, Ajenthan; Qazi, Hamood; Kumar, Atul; Mattoscio, Miriam; Chaudhuri, Abhijit; Sinha, Devesh
Abstract : Background: Cases of Amoebic encephalitis have been reported in countries with tropical climates. Here we describe a rare adult case in the UK with a rapidly progressive history, which was confirmed at autopsy. Case Presentation: A 77 year old lady, independent and still in employment, with a past medical history of Sjogren's syndrome, presented with sudden onset of slurred speech, left facial twitching and facial droop. MRI showed a right frontal enhancing lesion with surrounding vasogenic oedema. Dexametha- sone was started for suspected high grade neoplasm. Nine days later she had a temperature of 37.7°C, with no apparent source of systemic infection. Despite empirical treatment with antibiotics, she became progressively unresponsive over the next 72 hours, developing dense left hemiplegia. Repeat MRI head showed large widespread multifocal T2/FLAIR signal changes. A lesional biopsy was planned but she deteriorated rapidly and died. Post mortem revealed disseminated collections of amoebae throughout the cerebral hemispheres, brain stem and cerebellum. Discussion and Conclusions : Amoebic encephalitis, despite its rarity, should be a differential diagnosis in a rapidly progressive infective meningoencephalitis unresponsive to empirical therapy. Mortality is high, however early treatment based on clinical suspicion may improve survival rates. ajenthans@doctors.org.uk